Thrombospondin-1 is a major activator of TGF-β in fibrotic renal disease in the rat in vivo - Daniel, Christoph; Wiede, Julia; Krutzsch, Henry C.; Ribeiro, Solange M. F.; Roberts, David D.; Murphy-Ullrich, Joanne E.; Hugo, Christian (Kidney International, 2004)
Background. Transforming growth factor-β (TGF-β), a profibrotic cytokine involved in many scarring processes, has to be activated extracellularly before it can bind to its receptors. Thrombospondin 1 (TSP1), a multifunctional matricellular glycoprotein, has been identified as an activator of TGF-β in in vitro systems and during mouse postnatal development in vivo. TSP1 is expressed de novo in many inflammatory disease processes, including glomerular disease. Methods. In this study we investigated whether peptides specifically interfering with the activation process of TGF-β by TSP1 may be able to block activation of TGF-β in an in vivo model of mesangial proliferative glomerulonephritis. Results. Continuous intravenous infusion of blocking peptide by minipumps significantly reduced expression of active TGF-β in glomeruli on day 7 of disease as indicated by immunohistochemistry, bioassay, and activation of the TGF-β signal transduction pathway, while total TGF-β expression was unchanged. Inhibition of glomerular TGF-β activation was accompanied by a decrease of glomerular extracellular matrix accumulation and proteinuria, but was without effect on mesangial cell proliferation or influx of monocytes/macrophages. Conclusion. TSP1 is a major endogenous activator of TGF-β in experimental inflammatory glomerular disease. Drugs interfering with the activation of TGF-β by locally produced TSP1 may be considered as a future specific treatment of scarring kidney disease.
Created from Fastlane, Scopus look-up
Keywords: Extracellular matrix; Glomerulonephritis; TGF-β activation; Thrombospondin-1